Polymeric nanoparticles for targeted radiosensitization of prostate cancer cells. Issue 5 (14th August 2014) - Menon, Jyothi U.; Tumati, Vasu; Hsieh, Jer‐Tsong; Nguyen, Kytai T.; Saha, Debabrata
Abstract: One of the many issues of using radiosensitizers in a clinical setting is timing daily radiation treatments to coincide with peak drug concentration in target tissue. To overcome this deficit, we have synthesized a novel nanoparticle (NP) system consisting of poly (lactic‐co‐glycolic acid) (PLGA) NPs conjugated with prostate cancer cell penetrating peptide‐R11 and encapsulated with a potent radio‐sensitizer 8‐dibenzothiophen‐4‐yl‐2‐morpholin‐4‐yl‐chromen‐4‐one (NU7441) to allow prostate cancer‐specific targeting and sustained delivery over 3 weeks. Preliminary characterization studies showed that the R11‐conjugated NPs (R11‐NU7441 NPs) had an average size of about 274 ± 80 nm and were stable for up to 5 days in deionized water and serum. The NPs were cytocompatible with immortalized prostate cells (PZ‐HPV‐7). Further, the particles showed a bi‐phasic release of encapsulated NU7441 and were taken up by PC3 prostate cancer cells in a dose‐ and magnetic field‐dependent manner while not being taken up in nonprostate cancer cell lines. In addition, R11‐NU7441 NPs were effective radiation sensitizers of prostate cancer cell lines in vitro . These results thus demonstrate the potential of R11‐conjugated PLGA NPs as novel platforms for targeted radiosensitization of prostate cancer cells. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1632–1639, 2015.